Ultra-low material loss microstructure fiber for terahertz guidance - Hasan, Md. Rabiul; Ali, S.; Emi, S. A. (Photonics Letters of Poland, 2017)
In this letter, we numerically demonstrate a hybrid-core microstructure fiber for low-loss terahertz guidance. Finite element method with circular perfectly matched layer boundary condition is applied to characterize the guiding properties. It is shown that by using a triangular-core inside a square lattice microstructure exhibits ultra-low effective material loss (EML) of 0.169 dB/cm and low confinement loss of 0.087 dB/cm at the operating frequency of 0.75 THz. We also discuss how other guiding properties including power fraction, single mode propagation and dispersion vary with changing of core diameter and operating frequencies. This low-loss microstructure fiber can be effectively used in numerous applications in the THz regime. Full Text: PDF References J. J. Bai, J. N. Li, H. Zhang, H. Fang, S. J. Chang, "A porous terahertz fiber with randomly distributed air holes", Appl. Phys. B 103, 2 (2011). CrossRef S. Atakaramians, S. Afshar, B. M. Fischer, D. Abbott, T. M. Monro, "Porous fibers: a novel approach to low loss THz waveguides", Opt. Express 16, 12 (2008). CrossRef K. Wang, D. M. Mittleman, "Metal wires for terahertz wave guiding", Nature 432, 7015 (2004). CrossRef R. Islam, G. K. M. Hasanuzzaman, M. S. Habib, S. Rana, M. A. G. Khan, "Low-loss rotated porous core hexagonal single-mode fiber in THz regime", Opt. Fiber Technol. 24, (2015). CrossRef M. I. Hasan, S. M. A. Razzak, G. K. M. Hasanuzzaman, M. S.Habib, "Ultra-Low Material Loss and Dispersion Flattened Fiber for THz Transmission", IEEE Photon. Technol. Lett. 26, 23 (2014). CrossRef S. F. Kaijage, Z. Ouyang, X. Jin, "Porous-Core Photonic Crystal Fiber for Low Loss Terahertz Wave Guiding", IEEE Photon. Technol. Lett. 25, 15 (2013). CrossRef M. R. Hasan, M. A. Islam, A. A. Rifat, "A single mode porous-core square lattice photonic crystal fiber for THz wave propagation", J. Eur. Opt. Soc. Rapid Publ. 12, 1 (2016). CrossRef M. R. Hasan, M. A. Islam, M. S. Anower, S. M. A. Razzak, "Low-loss and bend-insensitive terahertz fiber using a rhombic-shaped core", Appl. Opt. 55, 30 (2016). CrossRef S. Ali et al. "Ultra-low loss THz waveguide with flat EML and near zero flat dispersion properties", in 9th Int. Conf. on Elect. and Comp. Eng., IEEE, (2016). CrossRef K. Nielsen, H. K. Rasmussen, A. J. Adam, P. C. Planken, O. Bang, P. U. Jepsen, "Bendable, low-loss Topas fibers for the terahertz frequency range", Opt. Express 17, 10 (2009). CrossRef A. W. Snyder, J. D. Love, Optical waveguide theory (London, Chapman & Hall 1983). DirectLink L. Vincetti, A. Polemi, in Antennas and Propagation Society International Symposium, IEEE (2009) G. P. Agrawal, Nonlinear fiber optics (Boston, Academic Press 1989). CrossRef B. S. Williams, "Terahertz quantum-cascade lasers", Nat. Photon. 1, 9 (2007). CrossRef H. W. Hubers et al. "Terahertz quantum cascade laser as local oscillator in a heterodyne receiver", Opt. Express 13, 15 (2005). CrossRef